Structural and grammatical peculiarities of the headline in modern ukrainian mass media - Marynenko, Iryna; Mykhailenko, Vladyslav (Słowo. Studia językoznawcze, 2019)
The article presents the grammatical structure of headlines of modern Ukrainian media. It is stated that traditional paper media continue the tradition of short headlines including non-extended simple sentences. They are often one- or two-word sentences, which intrigues and interests the reader. At the same time, cross-media editions show a tendency to use long titles in form of extended simple or composite sentences including the main content of the article. Sometimes too long headlines of publicistic materials can be an obstacle to remembering and understanding the sense of further information.